2011
DOI: 10.1088/0964-1726/20/5/055012
|View full text |Cite
|
Sign up to set email alerts
|

Vibration characteristics of electrorheological elastomer sandwich beams

Abstract: The vibration characteristics and control capabilities of a cantilever sandwich beam with electrorheological (ER) elastomers subjected to different electric fields are investigated in this study. Considering ER elastomers as viscoelastic damping materials with electrically controllable properties, a finite element model of a sandwich beam with an ER elastomer core is developed to predict the vibration responses of the proposed beam. An experimental analysis was also conducted to illustrate and evaluate the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 23 publications
0
37
0
Order By: Relevance
“…The acceleration responses of the MR/ER sandwich structures were measured by accelerometers mounted on the face layers. Although single-axis accelerometers were widely used to measure vibration responses of the structures (Allahverdizadeh et al, 2013c(Allahverdizadeh et al, , 2014Rajamohan et al, 2010aRajamohan et al, , 2010bRajamohan et al, , 2010c, application of laser sensors (Choi et al, 2010) and eddy current probe (Lee and Cheng, 1998;Wei et al, 2007Wei et al, , 2011 for measuring vibration displacement and laser vibrometer (Lara-Prieto et al, 2010) for measuring velocity have also been reported. The measured signals were analyzed in the signal analyzer and the natural frequencies and damping properties of the sandwich beam structures were subsequently identified from the peaks in the frequency response functions.…”
Section: Dynamic Characteristics Of Fully Treated Mr/er Sandwich Beammentioning
confidence: 99%
See 1 more Smart Citation
“…The acceleration responses of the MR/ER sandwich structures were measured by accelerometers mounted on the face layers. Although single-axis accelerometers were widely used to measure vibration responses of the structures (Allahverdizadeh et al, 2013c(Allahverdizadeh et al, , 2014Rajamohan et al, 2010aRajamohan et al, , 2010bRajamohan et al, , 2010c, application of laser sensors (Choi et al, 2010) and eddy current probe (Lee and Cheng, 1998;Wei et al, 2007Wei et al, , 2011 for measuring vibration displacement and laser vibrometer (Lara-Prieto et al, 2010) for measuring velocity have also been reported. The measured signals were analyzed in the signal analyzer and the natural frequencies and damping properties of the sandwich beam structures were subsequently identified from the peaks in the frequency response functions.…”
Section: Dynamic Characteristics Of Fully Treated Mr/er Sandwich Beammentioning
confidence: 99%
“…Finite element (FE) method is the most reported approach in vibration analysis of the MR/ER sandwich structures (Allahverdizadeh et al, 2012(Allahverdizadeh et al, , 2013a(Allahverdizadeh et al, , 2013c(Allahverdizadeh et al, , 2014Bishay et al, 2010;Hirunyapruk et al, 2010;Lee, 1995;Mohanty, 2013;Nayak et al, 2012b;Rajamohan et al, 2010aRajamohan et al, , 2010bRajamohan et al, , 2010cRajamohan et al, , 2013Rezaeepazhand and Pahlavan, 2008a;Wei et al, 2011;Zhou et al, 2006). This method employs potential and kinetic energy of the structures and represents the governing equations of motion in a matrix form as follows…”
Section: Mathematical Modeling Of Mr/er Sandwich Beam Structuresmentioning
confidence: 99%
“…Based on the model presented by Wei et al (2011), the effects of visoelastic properties of the ER elastomer are very small in the interested frequency range, and therefore, the imaginary portion of the shear modulus of the ER elastomer is not considered in this study. The numerically based effective medium method is used for determination of the out-of-plane effective mass density of the EMM (Zhu et al, 2011(Zhu et al, , 2014.…”
Section: Mapping Design Of a Beam Steering Of Flexural Wavesmentioning
confidence: 99%
“…In view of their composition and physical states, EREs can be considered solid analogues of ER fluids . In contract to that of ER fluids, the ER effect of EREs is expressed as the electric field controlled dynamic viscoelasticity; their storage modulus, loss modulus, and damping factors can be changed reversibly and quickly through the application of different electric fields . Because the carrier liquid of ER fluids is replaced by a polymer matrix in EREs, the sedimentation of particles and the leakage of liquid are avoided.…”
Section: Introductionmentioning
confidence: 99%
“…applied for a patent for the use of EREs to control structural vibrations in 1997. Bai et al . studied the dynamic performance of sandwich beams filled with EREs and used them as vibration attenuation devices.…”
Section: Introductionmentioning
confidence: 99%